Neutrophil-to-lymphocyte ratio is a prognostic marker in bladder cancer patients after radical cystectomy. Issue 1 (December 2016) - Kawahara, Takashi; Furuya, Kazuhiro; Nakamura, Manami; Sakamaki, Kentaro; Osaka, Kimito; Ito, Hiroki; Ito, Yusuke; Izumi, Koji; Ohtake, Shinji; Miyoshi, Yasuhide; Makiyama, Kazuhide; Nakaigawa, Noboru; et al.
Abstract Background There is no reliable biomarker for predicting the prognosis of patients who undergo radical cystectomy for bladder cancer. Recent studies have shown that the neutrophil-to-lymphocyte ratio (NLR) could function as a useful prognostic factor in several types of malignancies. This study aimed to assess the usefulness of NLR in bladder cancer. Methods A total of 74 patients who underwent radical cystectomy in our institutions from 1999 to 2014 were analyzed. The NLR was calculated using the patients' neutrophil and lymphocyte counts before radical cystectomy. An immunohistochemical analysis was also performed to detect tumor infiltrating neutrophils (CD66b) and lymphocytes (CD8) in bladder cancer specimens. Results A univariate analysis showed that the patients with a high NLR (≥2.38; HR = 4.84;p  = 0.007), high C-reactive protein level (>0.08; HR = 10.06;p  = 0.030), or pathological lymph node metastasis (HR = 4.73;p  = 0.030) had a significantly higher risk of cancer-specific mortality. Kaplan-Meier and log-rank tests further revealed that NLR was strongly correlated with overall survival (p  = 0.018), but not progression-free survival (p  = 0.137). In a multivariate analysis, all of these were found to be independent risk factors (HR = 4.62, 10.8, and 12.35, respectively). The number of CD8-positive lymphocytes was significantly increased in high-grade (p  = 0.001) and muscle-invasive (p  = 0.012) tumors, in comparison to low-grade and non-muscle-invasive tumors, respectively. Conclusions The NLR predicted the prognosis of patients who underwent radical cystectomy and might therefore function as a reliable biomarker in cases of invasive bladder cancer.